Age-Related Eye Diseases in Individuals With Mild Cognitive Impairment and Alzheimer's Disease - Chua, Jacqueline; Zhang, Zheting; Wong, Damon; Tan, Bingyao; Kulantayan, Bhavani; Sng, Chelvin C. A.; Hilal, Saima; Venketasubramanian, Narayanaswamy; Tan, Boon Yeow; Cheung, Carol Y.; Garhöfer, Gerhard; Popa-Cherecheanu, Alina; et al. (Frontiers in Aging Neuroscience, 2022)
Introduction: Alzheimer’s disease (AD) and age-related eye diseases pose an increasing burden as the world’s population ages. However, there is limited understanding on the association of AD/ cognitive impairment, no dementia (CIND) with age-related eye diseases. Methods: In this cross-sectional, memory clinic-based study of multiethnic Asians aged 50 and above, participants were diagnosed as AD (n=216), cognitive impairment, no dementia (CIND) (n=252), and no cognitive impairment (NCI) (n=124) according to internationally accepted criteria. Retinal photographs were graded for the presence of age-related macular degeneration (AMD) and diabetic retinopathy (DR) using standard grading systems. Multivariable-adjusted logistic regression models were used to determine the associations between neurological diagnosis and odds of having eye diseases. Results: Over half of the adults had at least one eye disease, with AMD being the most common (60.1%; n=356), followed by DR (8.4%; n=50). After controlling for age, sex, race, educational level, and marital status, persons with AD were more likely to have moderate DR or worse (OR=2.95, 95%CI=1.15-7.60) compared with NCI. In the fully adjusted model, neurological diagnosis was not associated with AMD (OR=0.75, 95%CI=0.45-1.24). Conclusions: Patients with AD have an increased odds of having moderate DR or worse, which suggests that these vulnerable individuals may benefit from specific social support and screening for eye diseases.